2018
DOI: 10.3897/zookeys.771.25534
|View full text |Cite
|
Sign up to set email alerts
|

Echinoderes pterus sp. n. showing a geographically and bathymetrically wide distribution pattern on seamounts and on the deep-sea floor in the Arctic Ocean, Atlantic Ocean, and the Mediterranean Sea (Kinorhyncha, Cyclorhagida)

Abstract: Kinorhynchs rarely show a wide distribution pattern, due to their putatively low dispersal capabilities and/or limited sampling efforts. In this study, a new kinorhynch species is described, Echinoderes pterus sp. n., which shows a geographically and bathymetrically wide distribution, occurring on the Karasik Seamount and off the Svalbard Islands (Arctic Ocean), on the Sedlo Seamount (northeast Atlantic Ocean), and on the deep-sea floor off Crete and on the Anaximenes Seamount (Mediterranean Sea), at a depth r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 41 publications
3
21
0
Order By: Relevance
“…Wide geographic distributions of E. multiporus and E. bispinosus species groups Despite their low motility and lack of a planktonic larval stage, many meiofauna are distributed quite widely and this phenomenon is referred as the 'meiofauna paradox' (Higgins & Thiel, 1988;Giere, 2009;Cerca et al, 2018). Recent investigations have revealed that the meiofauna paradox is present in Kinorhyncha at species-group or species level (Neuhaus & Sørensen, 2013;Herranz & Leander, 2016;Yamasaki et al, 2018aYamasaki et al, , 2019Randsø et al, 2019). This is also the case for the E. multiporus species group and the E. bispinosus species group (Figure 14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wide geographic distributions of E. multiporus and E. bispinosus species groups Despite their low motility and lack of a planktonic larval stage, many meiofauna are distributed quite widely and this phenomenon is referred as the 'meiofauna paradox' (Higgins & Thiel, 1988;Giere, 2009;Cerca et al, 2018). Recent investigations have revealed that the meiofauna paradox is present in Kinorhyncha at species-group or species level (Neuhaus & Sørensen, 2013;Herranz & Leander, 2016;Yamasaki et al, 2018aYamasaki et al, , 2019Randsø et al, 2019). This is also the case for the E. multiporus species group and the E. bispinosus species group (Figure 14).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, species are mostly reported from single localities and only a few species have broad distribution patterns, i.e. Echinoderes pterus Yamasaki et al, 2018a recorded from the Arctic Sea, Atlantic Ocean and Mediterranean Sea and Echinoderes unispinosus Yamasaki et al, 2018b from the Atlantic Ocean, Mediterranean Sea and East Pacific Ocean (Sørensen et al, 2018;Yamasaki et al, 2018aYamasaki et al, , 2018bYamasaki et al, , 2019. This general pattern of species being restricted to a confined geographic area is probably due to their low dispersal ability, or preference for a specific habitat (Artois et al, 2011;Sánchez et al, 2011Sánchez et al, , 2012; it should be said, however, that the scarcity of investigations could have prevented an unveiling of an ampler distribution for some species.…”
Section: Introductionmentioning
confidence: 99%
“…Echinoderes pterus is a species with a wide geographic distribution, ranging from the high Arctic, the North Atlantic, and into the Mediterranean Sea (Yamasaki et al, 2018a), and it has also been reported to show a wide bathymetric distribution, from 675 to 4403 m. Besides having this unusually wide range, E. pterus possesses a set of traits that easily distinguishes it from other congeners. The most characteristic is the presence of tufts of hairs on segment 9 -a structure unique for E. pterus.…”
Section: Remarksmentioning
confidence: 99%
“…A few years later Neuhaus and Sørensen (2013) reported Campyloderes cf. vanhoeffeni Zelinka (1913) in the Guinea Basin at 5064 m and in the southeastern deep-sea region of Canary Island at depths between 5055 m and 5118 m. Sánchez et al (2014a,b) described three additional species, i.e., Mixtophyes abyssalis Sánchez et al (2014a,b), Cristaphyes nubilis (Sánchez et al, 2014a,b), and Krakenella farinelli (Sánchez et al, 2014a,b), from the Guinea Basin, at depths between 5100-5175 m. The remaining and more recent reports of identified abyssal kinorhynchs are restricted to five areas: (1) abyssal plains, 3100-3300 m, around North Atlantic seamounts, from where Yamasaki et al (2019) describe Echinoderes kaempfae Yamasaki et al, 2019; (2) the East Mediterranean, 675-4403 m, from where Yamasaki et al (2018a) describe Echinoderes pterus Yamasaki et al, 2018a,b; (3) abyssal plains, 3351-5766, in the vicinity of the Kuril-Kamchatka Trench, from where Adrianov and Maiorova (2015 describe Cristaphyes abyssorum (Adrianov and Maiorova, 2015), Condyloderes kurilensis Adrianov and Maiorova (2016), Meristoderes okhotensis Adrianov and Maiorova (2018a), and Parasemnoderes intermedius Adrianov and Maiorova (2018b); (4) the abyssal plains, 3250-3853 m, off the Northwest American continental slope, from where Sørensen et al (2018) describe E. anniae, E. dubiosus, E. hamiltonorum, E. juliae, E. lupherorum, E. hviidarum, E. yamasakii, and Sørensen et al (2018Sørensen et al ( , 2019 report three additional known kinorhynch species, E. cf. unispinosus Yamasaki et al (2018a,b), Fissuroderes higginsi Neuhaus and Blasche (2006), and C. kurilensis; (5) the Clarion-Clipperton Fracture Zone, 4319-5012 m, in the tropical East Pacific, from where Sánchez et al (2019) describe Cephalorhyncha polunga, Echinoderes shenlong, and Meristoderes taro.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of Kinorhyncha from the deep sea have frequently reported unidentified species, mostly from the Indian, Pacific, and Atlantic Oceans (Neuhaus, 2013;Zeppilli et al, 2018). More recently, studies to the species level have received a strong boost, and up to 45 species have recently been described or reported from this environment (Neuhaus and Blasche, 2006;Sørensen, 2008a;Neuhaus and Sørensen, 2013;Sánchez et al, 2014aSánchez et al, ,b, 2019aAdrianov and Maiorova, 2015, 2016Sørensen, 2018, 2019;Sørensen and Grzelak, 2018;Sørensen et al, , 2019Yamasaki et al, 2018aYamasaki et al, ,b,c, 2019Cepeda et al, 2019a). Of these, some species seem to possess wider ranges of distribution than their congeners from the coastal zone.…”
Section: Introductionmentioning
confidence: 99%